2008
DOI: 10.1007/s00464-008-0218-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gastric pH in ambulatory esophageal pH monitoring

Abstract: There is an inverse, dose-dependent relationship between gastric pH and esophageal acid exposure. Negative 24-h esophageal pH test results for a patient with hypochlorhydria may prompt a search for nonacid reflux as the explanation for the patient's symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…10,11 The location of the upper border of the LES determined by HRM was variable when compared to the results of conventional manometry. Overall, there was only a moderate correlation between the two measurements with variation of as much as 3.4 cm noted.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The location of the upper border of the LES determined by HRM was variable when compared to the results of conventional manometry. Overall, there was only a moderate correlation between the two measurements with variation of as much as 3.4 cm noted.…”
Section: Discussionmentioning
confidence: 99%
“…The pH study was performed according to a previously described protocol. 16 Subjects and patients were instructed to follow a controlled diet, remain in an upright or sitting position until retiring to bed in the evening, avoiding eating or drinking between meals, refraining from chewing gum or smoking, perform normal activities at home or at work, and lie flat at night. All acid-suppressing medications were discontinued 3 (H2-blocking agents) or 14 days (PPIs) before the study.…”
Section: Esophageal Manometrymentioning
confidence: 99%
“…This assessment focuses on characterizing variation in baseline gastric pH, a key model parameter that determines the delivery of Cr(VI) to the SI, and subsequent risk, using published gastric pH data (Ayazi et al, 2009). Ayazi et al reported a bimodal distribution for gastric pH, with the normal subgroup distributed about a median pH of 1.7–1.8, and a hypochlorhydria subgroup with a median pH of approximately 4.2 (Figure 7).…”
Section: Resultsmentioning
confidence: 99%